RECOMMENDATIONS TO DEVELOP RESILIENCE AND SUSTAINABILITY THROUGH HIGHER EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGE TOWN, PENANG, April 2016 – Resilience and sustainability in societies are key concepts that can be effectively developed through education and higher education.